Effect of Internet Utilization on Overall Performance of Agricultural Research Scholars of M. P. University of Agriculture & Technology, Rajasthan - L. R. Choudhary , B. S. Bhimawat; H. K. Jain (Indian Journal of Extension Education, 2016)
Internet has become a way of life for majority of higher education students all around the world. For most universities and college students, the internet is a functional tool, one that has greatly changed the way they interact with each other and with information as they go about their studies. The Study revealed that data presented in table 1 it can be concluded that Majority of the internet utilizing male and female agricultural research scholars perceived that the “internet services facilitate improvement in systems of communication” as the most important effect on the academic performance and the “internet services facilitate to maintain a wide circle of friends” as the most important effect on the non-academic performance.